Rancang Bangun Alat Pendeteksi Kebocoran Gas LNG Menggunakan Sensor MQ-6 Pada Line Main Gas Header PLTDG Dengan Konektivitas ESP-8266 Berbasis Android - Edwin Josafat Pangaribuan; I Made Asna (Universitas Pendidikan Nasional, 2020)
To make electrical energy, a power plant is needed to produce it, in the current era where pollution is increasing which results in global warming, environmentally friendly power plants are being intensified, one of which is PLTDG where 99% of the fuel is LNG, which is one of the environmentally friendly energies that produces lowest emissions. In using LNG, it also needs to be supported by safety equipment to maintain the safety, security of workers and power plant, so a safety system is needed to monitor the condition of the gas distribution installation to remain safe from LNG gas leaks. This research aims to produce a design for detecting LNG gas leaks in gas installations such as gas connections and pipes using the MQ-6 sensor as a gas sensor, and the ESP 8266 as a module on the Arduino Uno microcontroller to connect Arduino to the internet via wifi. The way this tool works is, when the MQ-6 sensor detects LNG gas, the sensor will send data to Arduino Uno and display it on the LCD screen, in experiments that have been carried out the buzzer and led provide an alarm notification when the leakage measurement reaches the 400ppm set point, Average gas leakage value at 640ppm in experimental data, this tool sends information on gas leakage data to Thinkspeak and then sends data to Android smartphone with a response range of 6-9 seconds from the leakage value reading.